THE GENERALIZED METHODS OF THE ANALYSIS OF DYNAMIC PROPERTIES OF ECONOMIC SYSTEMS - Tamara Viktorovna Tatochenko; Eugeniy L’vovich Toroptsev (Вестник Северо-Кавказского федерального университета, 2022)
The mathematical apparatus of the analysis of own dynamic properties of economic systems is given in article.